How Reliable are 11- to 13-Year-Olds’ Self-Ratings of Effort in Noisy Conditions? - Visentin, Chiara; Prodi, Nicola (Frontiers in Built Environment, 2021)
Performing a task in noisy conditions is effortful. This is especially relevant for children in classrooms as the effort involved could impair their learning and academic achievements. Numerous studies have investigated how to use behavioral and physiological methods to measure effort, but limited data are available on how well school-aged children rate effort in their classrooms. This study examines whether and how self-ratings can be used to describe the effort children perceive while working in a noisy classroom. This is done by assessing the effect of listening condition on self-rated effort in a group of 182 children 11-13 years old. The children performed three tasks typical of daily classroom activities (speech perception, sentence comprehension, and mental calculation) in three listening conditions (quiet, traffic noise, and classroom noise). After completing each task, they rated their perceived task-related effort on a five-point scale. Their task accuracy and response times (RTs) were recorded (the latter as a behavioral measure of task-related effort). Participants scored higher (more effort) on their self-ratings in the noisy conditions than in quiet. Their self-ratings were also sensitive to the type of background noise, but only for the speech perception task, suggesting that children might not be fully aware of the disruptive effect of background noise. A repeated-measures correlation analysis was run to explore the possible relationship between the three study outcomes (accuracy, self-ratings, and RTs). Self-ratings correlated with accuracy (in all tasks) and with RTs (only in the speech perception task), suggesting that the relationship between different measures of listening effort might depend on the task. Overall, the present findings indicate that self-reports could be useful for measuring changes in school-aged children’s perceived listening effort. More research is needed to better understand, and consequently manage, the individual factors that might affect children’s self-ratings (e.g., motivation) and to devise an appropriate response format.